Odpowiedź :
Nie ma tu podanej wartościowości srebra więc są dwa sposoby wykonania tego równania.
1) srebro(I)
• AgNO₃ + KI → AgI↓ + KNO₃
• Ag⁺ + NO₃⁻ + K⁺ + I⁻ → AgI↓ + K⁺ + NO₃⁻
• Ag⁺ + I⁻ → AgI↓
2) srebro(II)
• Ag(NO₃)₂ + 2 KI → AgI₂↓ + 2 KNO₃
• Ag²⁺ + 2 NO₃⁻ + 2 K⁺ + 2 I⁻ → AgI₂↓ + 2 K⁺ + 2 NO₃⁻
• Ag²⁺ + 2 I⁻ → AgI₂↓
1) srebro(I)
• AgNO₃ + KI → AgI↓ + KNO₃
• Ag⁺ + NO₃⁻ + K⁺ + I⁻ → AgI↓ + K⁺ + NO₃⁻
• Ag⁺ + I⁻ → AgI↓
2) srebro(II)
• Ag(NO₃)₂ + 2 KI → AgI₂↓ + 2 KNO₃
• Ag²⁺ + 2 NO₃⁻ + 2 K⁺ + 2 I⁻ → AgI₂↓ + 2 K⁺ + 2 NO₃⁻
• Ag²⁺ + 2 I⁻ → AgI₂↓